SIGNIFIKASI SPIRITUALITAS KRISTEN: SEBUAH USAHA PEMBINAAN KEROHANIAN WARGA GEREJA KELOMPOK USIA MUDA - Marinus Nangi Kewa; David Eko Setiawan; Panus Hilapok; Daen Rabecca (Sekolah Tinggi Teologi Baptis Medan, 2021)
The aim of this research is to provide suggestions on how the church should strive to guide young people so that they experience spiritual growth. This research was conducted with a literature study method and a qualitative approach. This is because young people are the spearhead in determining the growth of the church, both in ministry and as a successor in the church itself. However, the problem that occurs today is the lack of guidance for young people, both from the role of spiritual coaches, especially in the formation of parents. So that this results in a decline in the spirituality of young people. The training of young people can be done by the church by teaching the truth of God's Word, instilling fear of God, setting the right example, holding a community worship program, teaching them to respect others. So that the results obtained from this coaching effort are able to increase the spiritual growth of young people, especially in the correct knowledge and fellowship of the Lord Jesus so that they are able to become people who can be role models and become a continuation of ministry in the church and become a blessing for everyone around them.